Temporal Variation of the Shortwave Spherical Albedo of the Earth - Penttilä, A.; Muinonen, K.; Ihalainen, O.; Uvarova, E.; Vuori, M.; Xu, G.; Näränen, J.; Wilkman, O.; Peltoniemi, J.; Gritsevich, M.; Järvinen, H.; Marshak, A. (Frontiers in Remote Sensing, 2022)
The Earth’s spherical albedo describes the ratio of light reflected from the Earth to that incident from the Sun, an important variable for the Earth’s radiation balance. The spherical albedo has been previously estimated from satellites in low-Earth orbits, and from light reflected from the Moon. We developed a method to derive the Earth’s spherical shortwave albedo using the images from the Earth Polychromatic Imaging Camera (EPIC) on board National Oceanic and Atmospheric Administration’s (NOAA) Deep Space Climate Observatory (DSCOVR). The satellite is located in the Lagrange 1 point between the Earth and the Sun and observes the complete illuminated part of the Earth at once. The method allows us to provide continuously updated spherical albedo time series data starting from 2015. This time series shows a systematic seasonal variation with the mean annual albedo estimated as 0.295±0.008 and an exceptional albedo maximum in 2020, attributed to unusually abundant cloudiness over the Southern Oceans.